Vanadyl(acetylacetonate)2 mediated hydrolytic splitting of 1,3,5-triazine in a solution of toluene at 130 °C: The crystal structure of its axial formamide adduct - Arslan, Evrim; Bernal, Ivan; Lalancette, Roger (European Journal of Chemistry, 2022)
A toluene reaction of vanadyl bis(acetylacetonate) with 1,3,5-triazine produces a symmetrical three-fold hydrolytic cleavage of the triazine, and these three formamide moieties are found in the crystal structure. One of the resulting formamides attaches itself to the sixth (axial) position of the vanadyl complex, producing materials in which the remaining two formamides are trapped in the resulting lattice. Those crystals belong in space group Pca21, Z = 4 and the final R-factor = 0.030 for 3213 data collected at 100 K.